T Cell Responses and Regulation and the Impact of In Vitro IL‐10 and TGF‐β Modulation During Treatment of Active Tuberculosis. (February 2017) - Feruglio, S. L.; Kvale, D.; Dyrhol‐Riise, A. M.
Abstract: Mycobacterium tuberculosis ( Mtb ) is particularly challenging for the immune system being an intracellular pathogen, and a variety of T cell subpopulations are activated by the host defence mechanism. In this study, we investigated T cell responses and regulation in active TB patients with drug‐sensitive Mtb (N = 18) during 24 weeks of efficient anti‐TB therapy. T cell activation, differentiation, regulatory T cell (Treg) subsets, Mtb ‐induced T cell proliferation and in vitro IL‐10 and TGF‐ β modulation were analysed by flow cytometry at baseline and after 8 and 24 weeks of therapy, while soluble cytokines in culture supernatants were analysed by a 9‐plex Luminex assay. Successful treatment resulted in significantly reduced co‐expression of HLA‐DR/CD38 and PD‐1/CD38 on both CD4 + and CD8 + T cells, while the fraction of CD4 + CD25 high CD127 low Tregs ( P = 0.017) and CD4 + CD25 high CD127 low CD147 + Tregs ( P = 0.029) showed significant transient increase at week 8. In vitro blockade of IL‐10/TGF‐ β upon Mtb antigen stimulation significantly lowered the fraction of ESAT‐6‐specific CD4 + CD25 high CD127 low Tregs at baseline ( P = 0.047), while T cell proliferation and cytokine production were unaffected. Phenotypical and Mtb ‐specific T cell signatures may serve as markers of effective therapy, while the IL‐10/TGF‐ β pathway could be a target for early inhibition to facilitate Mtb clearance. However, larger clinical studies are needed for verification before concluding.